Triple positive solutions for semipositone fractional differential equations m-point boundary value problems with singularities and p–q-order derivatives - Zhang, Xingqiu; Shao, Zhuyan; Zhong, Qiuyan; Zhao, Zengqin (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, by means of Leggett–Williams and Guo–Krasnosel’skii fixed point theorems, together with height functions of the nonlinearity on different bounded sets, triple positive solutions are obtained for some fractional differential equations with p–q-order derivatives involved in multi-point boundary value conditions. The nonlinearity may not only take negative infinity but also may permit singularities on both the time and the space variables.